CSR Reporting for Socially Responsible Investors - Arshad, Asra (2015)
This paper aims to explore the composition of effective CSR reporting for SRI investors in the United States. With the growth of socially responsible investment (SRI), the need to address SRI investors’ information needs through corporate CSR reporting is ever more pressing. Using an inductive content analysis, critical reporting themes were identified and discussed with academics and professionals in the field of CSR reporting and SRI. Through the findings, a framework for CSR reporting in the context of SRI decision-making was formulated, in which the identification and mitigation of material issues was found to be the cornerstone of an effective report. Other reporting themes which SRI investors find particularly useful in their investment analysis and decision making were- ‘effect of social and environmental factors on financial performance’, ‘issues addressed are central to corporate strategy’, ‘risk and opportunities of environmental and social impact addressed’, ‘identification of processes within the value chain with their respective impacts’, ‘performance data (Y-to-Y)’, ‘comprehensive key performance indicators’, ‘adherence to GRI guidelines’, ‘adherence to industry standards and international initiatives’ and ‘engagement in public policy on social and/or environmental issues’. Interview insights stressed upon the heterogeneity of the SRI investment community in which different investors hold varied perceptions and values related to sustainability. In order to influence SRI decision-making, companies need to understand the perceptions and values of their specific group of SRI investors. This can take place through active investor engagement in which two-way communication is formed between the company and its SRI investors. It was concluded that integrated reporting is the future of stand-alone CSR reporting as the format encompasses many of the reporting themes presented by the framework. Integrated reporting strives to establish a link between the company’s sustainability performance and the financial bottom line and it shows how sustainability issues are related to the corporate strategy.